Metamorphism of chromitites in the Tapo ultramafic massif, eastern Cordillera, Peru - Fanlo González, Isabel (2009)
Metamorphosed chromite crystals in massive chromitite ore-bodies from the Tapo ultramafic massif (Peru) show distinct petrographic features and chemical patterns of zoning different from those exhibited by disseminated chromites. The observed differences can be explained in terms of prograde metamorphism up to the lower-amphibolite facies, under the control of the chromite/silicate ratio, chromite grain size and degree of fracturing.